1979
DOI: 10.1159/000112441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anticonvulsant Drugs on Chick Embryonic Neurons and Glia in Cell Culture

Abstract: The responses of neurons and glial cells to diphenylhydantoin (DPH), 5-(p-hydroxyphenyl)-5-phenylhydantoin (HPPH) and phenobarbital were studied in cell cultures of dissociated chick embryo brain. Drugs were added to cultures daily for 3 days in concentrations ranging from 1 x 10–4 to 1 x 10–3M. Histological evaluations revealed that cultures treated with DPH exhibited fewer cell aggregates, fewer neurons and less prominent neuronal processes. Preliminary studies suggested that the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
1
2
1
Order By: Relevance
“…Phenobarbital, however, appeared to be a relatively poor inhibitor. Culver and Vernadakis (1979), using neuronal cultures derived from chick brain at different stages of development, observed that [14C]leucine incorporation into pro-tein was decreased in the presence of phenytoin but not phenobarbital and confirms the observations of Swaiman and Stright (1973). Further, these authors also showed that phenytoin (but not phenobarbital) has a direct effect on the organization and development of brain cells and that neurons are particularly susceptible to the cytotoxic effects of phenytoin.…”
Section: Discussionsupporting
confidence: 71%
“…Phenobarbital, however, appeared to be a relatively poor inhibitor. Culver and Vernadakis (1979), using neuronal cultures derived from chick brain at different stages of development, observed that [14C]leucine incorporation into pro-tein was decreased in the presence of phenytoin but not phenobarbital and confirms the observations of Swaiman and Stright (1973). Further, these authors also showed that phenytoin (but not phenobarbital) has a direct effect on the organization and development of brain cells and that neurons are particularly susceptible to the cytotoxic effects of phenytoin.…”
Section: Discussionsupporting
confidence: 71%
“…Even though morphological evaluation of glial cells has suggested an apparent lack of sensitivity to the toxic effects of anticonvulsant drugs [37], the biochemical results in our study have shown that glial cells were affected by the drugs. We found that phenytoin inhibited both CNP and CA activities in vivo, whereas valproate increased CNP activity both in vivo and in vitro.…”
contrasting
confidence: 71%
“…Changes in glu cose metabolism and cognitive function may well be secondary manifestations of other biochemical effects of phenytoin. Phenytoin, for example, de creases cellular protein synthesis in a number of models of the developing nervous system (Swaiman and Stright, 1973;Jones and Woodbury, 1976;Culver and Vernadakis, 1979;Yanagihara and Hamberger, 1979). The most important effect of the drug appears to be on ionic fluxes across cellular and subcellular membranes (Woodbury, 1980).…”
Section: Discussionmentioning
confidence: 99%